Recombinant Slit2 Reduces Surgical Brain Injury Induced Blood Brain Barrier Disruption via Robo4 Dependent Rac1 Activation in a Rodent Model - Prativa Sherchan (Nature Portfolio, 2017)
Abstract Brain tissue surrounding surgical resection site can be injured inadvertently due to procedures such as incision, retractor stretch, and electrocauterization when performing neurosurgical procedures, which is termed as surgical brain injury (SBI). Blood brain barrier (BBB) disruption due to SBI can exacerbate brain edema in the post-operative period. Previous studies showed that Slit2 exhibited vascular anti-permeability effects outside the brain. However, BBB protective effects of Slit2 following SBI has not been evaluated. The objective of this study was to evaluate whether recombinant Slit2 via its receptor roundabout4 (Robo4) and the adaptor protein, Paxillin were involved in reducing BBB permeability in SBI rat model. Our results showed that endogenous Slit2 increased in the surrounding peri-resection brain tissue post-SBI, Robo4 remained unchanged and Paxillin showed a decreasing trend. Recombinant Slit2 administered 1 h before injury increased BBB junction proteins, reduced BBB permeability, and decreased neurodeficits 24 h post-SBI. Furthermore, recombinant Slit2 administration increased Rac1 activity which was reversed by Robo4 and Paxillin siRNA. Our findings suggest that recombinant Slit2 reduced SBI-induced BBB permeability, possibly by stabilizing BBB tight junction via Robo4 mediated Rac1 activation. Slit2 may be beneficial for BBB protection during elective neurosurgeries.